A Ferroelectric Iron(II) Spin Crossover Material. (4th October 2017) - Jornet‐Mollá, Verónica; Duan, Yan; Giménez‐Saiz, Carlos; Tang, Yuan‐Yuan; Li, Peng‐Fei; Romero, Francisco M.; Xiong, Ren‐Gen
Abstract: A dual‐function material in which ferroelectricity and spin crossover coexist in the same temperature range has been obtained. Our synthetic strategy allows the construction of acentric crystal structures in a predictable way and is based on the high directionality of hydrogen bonds. The well‐known iron(II) spin crossover complex [Fe(bpp)2 ] 2+ (bpp=2, 6‐bis(pyrazol‐3‐yl)pyridine), a four‐fold noncentrosymmetric H‐bond donor, was combined with a disymmetric H‐bond acceptor such as the isonicotinate (isonic) anion to afford [Fe(bpp)2 ](isonic)2 ⋅2 H2 O. This low‐spin iron(II) compound crystallizes in the acentric nonpolar I 4 ‾ space group and shows piezoelectricity and SHG properties. Upon dehydration, it undergoes a single‐crystal to single‐crystal structural rearrangement to a monoclinic polar Pc phase that is ferroelectric and exhibits spin crossover.